Problematika Peningkatan Kemampuan Baca Tulis Al-Qur’an Siswa di SMP Negeri 1 Percut Sei Tuan - Hidayat, M. Nuha; As’ad, As’ad (Kamaya: Jurnal Ilmu Agama, 2025)
This study aims to analyze the condition of students' Qur'an literacy, identify inhibiting factors, and formulate solution efforts at SMP Negeri 1 Percut Sei Tuan. This study uses a qualitative method with a phenomenological approach, collecting data through in-depth interviews, observations, and documentation studies. Data analysis was carried out using the Miles and Huberman models. The results of the study show that students' Qur'an literacy skills are at a low to moderate level, where most students still have difficulty reading with correct tajweed and writing Arabic letters correctly. The main inhibiting factors are divided into internal and external. Internally, the cause is low student motivation and lack of basic knowledge due to diverse religious educational backgrounds. Externally, the main obstacles come from the lack of parental support and supervision as well as limited time and facilities at school. To overcome this problem, comprehensive efforts are needed. Based on the findings, the proposed solutions include the addition of special lesson hours for reading and writing the Qur'an, the use of digital media for interactive learning, and the application of more practical learning methods. Although various proposals have been submitted by teachers, their implementation has not yet been fully realized. This study concludes that collaboration between schools, teachers, and families is crucial to improve students' Qur'an literacy effectively and sustainably.